Tea cultivation: facilitating soil organic carbon accumulation and altering soil bacterial community—Leishan County, Guizhou Province, Southwest China - Yingge Shu; Shan Xie; Hong Fan; Chun Duan; Yuansheng Liu; Zuyong Chen (PeerJ)
Background Camellia sinensis is an important cash crop in southwestern China, with soil organic carbon playing a vital role in soil fertility, and microorganisms contributing significantly to nutrient cycling, thus both of them influencing tea tree growth and development. However, existing studies primarily focus on soil organic carbon, neglecting carbon fractions, and the relationship between soil organic carbon fractions and microbial communities is unclear. Consequently, this study aims to clarify the impact of different tea planting durations on soil organic carbon fractions and microbial communities and identify the main factors influencing microbial communities. It provides a theoretical basis for soil quality evaluation in the study area and scientific guidance for tea plantation management, thus fostering the region’s economic sustainability. Methods This study selected tea plantations with different tea planting durations of 3–5 years (Y5), 12–16 years (Y15), 18–22 years (Y20), 40–42 years (Y40), and 48–50 years (Y50), as research subjects and adjacent uncultivated forest without a history of tea planting (CK) served as controls. Soil organic carbon (SOC), particulate organic carbon (POC), easily oxidizable organic carbon (EOC), dissolved organic carbon (DOC), microbial biomass carbon (MBC), and bacterial diversity were measured in the 0–20 cm and 20–40 cm soil layers, respectively. Results Compared to the adjacent uncultivated forest (CK), the soil organic carbon (SOC), easily oxidizable carbon (EOC), particulate organic carbon (POC), and dissolved organic carbon (DOC) contents in a 40-year tea plantation significantly increased. Nonetheless, the microbial biomass carbon (MBC) content notably decreased. POC/SOC ratios rose with prolonged planting, signifying enhanced conversion of organic carbon into particulate forms. Bacterial community diversity peaked at 15 years and declined by 40 years post-planting and after tea planting dominated by Acidobacteriota, Chloroflexi, Proteobacteria, and Actinobacteriota in the tea garden. FAPROTAX analysis highlighted aerobic and anaerobic chemoheterotrophy, cellulolysis, and nitrogen fixation as key bacterial functions. POC and MBC significantly influenced bacterial community structure. In conclusion, tea plantation soil exhibited the highest organic carbon content at 40 years of tea planting, indicating strong carbon accumulation capacity. However, soil acidification in the tea plantation may affect changes in organic carbon and bacterial community. Therefore, in the tea planting process, it is necessary to improve the management system of tea plantations to ensure the maintenance of a good ecological environment in the tea plantation soil, thus achieving sustainable development of the tea industry in the region.